Insularity promotes plant persistence strategies in edaphic island systems. Issue 4 (17th February 2022) - Conti, Luisa; Méndez‐Castro, Francisco E.; Chytrý, Milan; Götzenberger, Lars; Hájek, Michal; Horsák, Michal; Jiménez‐Alfaro, Borja; Klimešová, Jitka; Zelený, David; Ottaviani, Gianluigi
Abstract: Aim: Trait‐based approaches are being used increasingly in island biogeography, providing key insights into the eco‐evolutionary dynamics of insular systems. However, the determinants of persistence of plant species after they have arrived and established on an island remain largely unexplored. Here, we used three edaphic island systems (i.e., habitat patches distinguished from the landscape matrix by distinct soil conditions and specialized vegetation) to examine relationships between persistence strategies (those associated with clonality, bud bank, seed mass and life‐form) and insularity. We hypothesized that insularity promotes and selects strategies to persist locally, such that species occurring on small and/or isolated edaphic islands show trait values indicative of enhanced persistence and lower functional diversity. Location: Three European systems of edaphic islands in the Western Carpathians, Moravia and the Cantabrian Range. Time period: Present. Major taxa studied: Vascular plants. Methods: For each system, we used linear models to explore persistence‐related plant trait patterns (mean trait values and functional diversity) in relationship to three insularity metrics (island size, isolation and target effect). We focused on patterns of edaphic island specialists because their presence is confined to the islands. Results: We found that insularity metrics largely explained the variation of the mean value and diversity of persistence‐related traits of edaphic island plant specialists. Specifically, insularity was positively related to traits supporting local persistence (e.g., more extensive lateral spread) and to a reduced variability in persistence traits. More insular systems showed stronger and more numerous trait–insularity links. Main conclusions: Insularity can affect plant species diversity, form and function in edaphic island systems, such as selecting for enhanced and less diverse persistence strategies. Plant species occurring in insular systems might therefore avoid or delay local extinction by promoting adaptive strategies to persist in situ .